A prospective, randomized, comparison of the coronary vasomotion associated with drug-coated balloon versus drug-eluting stent. (25th November 2020) - Kawai, T; Yamada, T; Watanabe, T; Morita, T; Furukawa, Y; Tamaki, S; Kawasaki, M; Kikuchi, A; Seo, M; Nakamura, J; Kayama, K; Kawahira, M; et al.
Abstract: Background: It is widely known that even new-generation drug-eluting stent (DES) induce coronary vasomotion abnormality. On the other hand, recent studies reported that drug-coated balloon (DCB) for native coronary artery was non-inferior to DES in medium term outcomes. However, there is no available information about vasomotion after treatment with DCB. Purpose: The aim of this study was to prospectively compare coronary vasomotion in patients treated with DCB versus new-generation DES. Methods: Twenty-seven patients were randomly treated with angioplasty with DCB (n=12) versus implantation of bioabsorbable polymer everolimus-eluting stent (BP-EES, n=15) after successful predilation. At 8 months after treatment, endothelium-dependent and -independent vasomotion were evaluated by intracoronary infusion of incremental doses of acetylcholine (for right coronary artery: low-dose 5μg, high-dose 50μg and for left coronary artery: low-dose 10μg, high-dose 100μg) and nitroglycerine (200μg). Mean luminal diameter of the distal segments, beginning 5 mm and ending 15 mm distal to the edge of the treated segment was quantitatively measured by angiography. Results: Clinical and procedural characteristics were not different between two groups. Vasoconstriction after acetylcholine infusion was less pronounced in the DCB group than the BP-EES group (low-dose: 4±13% vs −4±14%, p=0.158, high-dose: −2±14% vs −28±30%, p=0.013). The response to nitroglycerin was not different between two groups (17±13% vs 18±24%, p=0.838). Conclusion: Vasoconstriction after acetylcholine infusion in the peri-treated region was more pronounced in the BP-EES group than in the DCB group, which suggests that endothelial function of coronary vessel treated by DCB can be more preserved than new-generation DES. Funding Acknowledgement: Type of funding source: None